2016
DOI: 10.3390/ma9030175
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Dexamethasone-Loaded Electrospun Nanofiber Sheets as a Sustained Drug Delivery System

Abstract: Recently, electrospinning technology has been widely used as a processing method to make nanofiber sheets (NS) for biomedical applications because of its unique features, such as ease of fabrication and high surface area. To develop a sustained dexamethasone (Dex) delivery system, in this work, poly(ε-caprolactone-co-l-lactide) (PCLA) copolymer with controllable biodegradability was synthesized and further utilized to prepare electrospun Dex-loaded NS using water-insoluble Dex (Dex(b)) or water-soluble Dex (De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Thus, tailoring the PLLA into the PCL segment can change the melting points of PLC. Consistent with this idea, we previously found that incorporation of the PLLA into the PCL segment decreased melting points by decreasing crystalline aggregation of the PCL segment interrupted by PLLA [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 53%
“…Thus, tailoring the PLLA into the PCL segment can change the melting points of PLC. Consistent with this idea, we previously found that incorporation of the PLLA into the PCL segment decreased melting points by decreasing crystalline aggregation of the PCL segment interrupted by PLLA [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 53%
“…The low water solubility of dexamethasone made us encapsulate in nanofibers and study its solubility and bioavailability. The nanofiber-based delivery of dexamethasone can be easy and feasible [ 64 ]. The electrospinning process ensured the uniform distribution of dexamethasone in nanofibers.…”
Section: Resultsmentioning
confidence: 99%
“…There are lots of factors that could promote the growth of osteoblasts, such as extracellular vesicles (EVs), which can promote osteogenic function through the regulation of osteoblast differentiation and expression of osteogenic genes in vitro [15]; BMP-2 can induce bone marrow mesenchymal stem cells to differentiate into osteoblasts and promote the proliferation of osteoblasts. Mikami et al proved that BMP-2 and DEX can support the osteogenic differentiation of bone marrow mesenchymal stem cells in vitro and jointly adding BMP-2 and DEX (a synthetic glucocorticoid [16]) to biomaterials may enhance their osteogenic differentiation efficacy in clinical bone tissue engineering [17]. It has also been proved that it is very important in bone tissue engineering to maintain their concentration of action, prolong their effectiveness, reduce the systemic risk of high burst release, and control the release of growth factors from biomaterial scaffolds [18].…”
Section: Introductionmentioning
confidence: 99%